Bachelor students’ soft skills development in course of foreign language instruction - Svetlana G. Men’shenina; Galina A. Pozdnyakova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Currently there is a demand for specialists with developed soft skills which is due to relevant economic situation, increasing information flows and dynamic processes in the professional environment, as well as employers’ requirements. Thus, high quality education for future university graduates with universal competencies that can be useful in many life situations is required. The purpose of the article is to explain the need for soft skills development in course of foreign language instruction as one of the conditions for professional training enhancement. Soft skills are a complex phenomenon that includes four categories. The category under study is focused on thinking skills, which, in turn, are related to different types of effective thinking: analytical, logical, critical, systemic, creative, structural, project, tactical and strategic thinking, as well as information search and analysis, decision making. The authors of the article consider the technology of critical thinking development through reading as an effective means of soft skills development at bachelor students’ of various areas of training. Testing assessment demonstrated that most students’ critical thinking performance is at low level. Thinking skills under discussion were improved by means of reading authentic texts and doing exercises of various types: instruction, reconstruction, search. Teaching experiment confirmed the hypothesis that process of soft skills development should be effective if purposeful and consistent work is carried out to form bachelor students’ critical thinking skills in course of foreign language instruction at the university.